PENGARUH MODEL JOYFUL LEARNING BERBANTUAN MEDIA PAPAN PINTAR MATEMATIKA TERHADAP PEMAHAMAN KONSEP KPK DAN FPB PADA SISWA KELAS V SDN 47 MATARAM - Ghaitsa Zahira Shofa; Muhammad Makki; Baiq Yuni Wahyuningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low level of elementary school students’ conceptual understanding in mathematics, particularly on the topics of Least Common Multiple (LCM) and Greatest Common Divisor (GCD), remains a significant issue that may affect students’ success in learning more advanced mathematical concepts. This study aimed to determine the effect of the Joyful Learning model assisted by the Mathematics Smart Board (PAPINKA) on students’ understanding of LCM and GCD concepts. This research employed a quantitative approach with a pre-experimental method using a One Group Pretest-Posttest Design. The sample consisted of 35 fifth-grade students of SDN 47 Mataram. Data were collected through tests and observations and analyzed using descriptive and inferential statistics, including the Shapiro-Wilk normality test, paired sample t-test, and effect size analysis. The results showed that the mean score increased from 50.26 on the pretest to 74.71 on the posttest. The normality test results indicated significance values of 0.060 for the pretest and 0.071 for the posttest, showing that the data were normally distributed. The paired sample t-test yielded a significance value of 0.001 (< 0.05), indicating a significant effect of the Joyful Learning model assisted by PAPINKA on students’ understanding of LCM and GCD concepts. Furthermore, the effect size value of 2.572 was categorized as large, indicating a strong effect of the treatment. Therefore, the Joyful Learning model assisted by the Mathematics Smart Board (PAPINKA) was found to be effective in improving elementary school students’ understanding of LCM and GCD concepts.